Case report: Treatment of advanced CSF1-receptor associated leukoencephalopathy with hematopoietic stem cell transplant - Bergner, Caroline G.; Schäfer, Lisa; Vucinic, Vladan; Schetschorke, Birthe; Lier, Julia; Scherlach, Cordula; Rullmann, Michael; Sabri, Osama; Classen, Joseph; Platzbecker, Uwe; Kühl, Jörn-Sven; Barthel, Henryk; et al. (Frontiers in Neurology, 2023)
CSF1 receptor-related leukoencephalopathy is a rare genetic disorder presenting with severe, adult-onset white matter dementia as one of the leading symptoms. Within the central nervous system, the affected CSF1-receptor is expressed exclusively in microglia cells. Growing evidence implicates that replacing the defective microglia with healthy donor cells through hematopoietic stem cell transplant might halt disease progression. Early initiation of that treatment is crucial to limit persistent disability. However, which patients are suitable for this treatment is not clear, and imaging biomarkers that specifically depict lasting structural damage are lacking. In this study, we report on two patients with CSF1R-related leukoencephalopathy in whom allogenic hematopoietic stem cell transplant at advanced disease stages led to clinical stabilization. We compare their disease course with that of two patients admitted in the same timeframe to our hospital, considered too late for treatment, and place our cases in context with the respective literature. We propose that the rate of clinical progression might be a suitable stratification measure for treatment amenability in patients. Furthermore, for the first time we evaluate [18F] florbetaben, a PET tracer known to bind to intact myelin, as a novel MRI-adjunct tool to image white matter damage in CSF1R-related leukoencephalopathy. In conclusion, our data add evidence for allogenic hematopoietic stem cell transplant as a promising treatment in CSF1R-related leukoencephalopathy patients with slow to moderate disease progression.